HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KEMANDIRIANÂ LANSIA DALAM PEMENUHAN PERSONAL HYGIENE DI DESA PRAJEKAN KIDUL BONDOWOSO - Sudarsih, Sri; Ria Sandika, Denny (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Elderly suffered physical deterioration and social changes that cause dependence on self-reliance. Elderly who are accustomed activity will be more independent than the elderly dependency. Family support is an attitude, action, and acceptance of the family members. The aim of research to determine the relationship between family support to the independence of the elderly in the fulfillment of personal hygiene. The study design used in this research is the design of an analytic study with cross sectional. The population in this study are all families who have elderly people in the village of Bondowoso Kidul Prajekan as many as 61 people. Samples were taken using purposive samlping as many as 53 respondents. Variabel correlational studies that support the family as an independent variable and the independence of the elderly in the fulfillment of personal hygiene as the dependent variable. Instruments used in collecting data in this study was a questionnaire and analyzed using Spearman rho test with SPSS version 16.0 statistical. The results obtained showed that the value of rhitung of 0,579> 0,266 rtabel while the correlation coefficient of 0.000 <a 0.05, p <a so H0 and H1 accepted means no relationship between the Family Support the Independence of the Elderly in the Personal Hygiene Compliance in Prajekan Kidul village of Bondowoso. It shows family support can affect the independence of the elderly and the fulfillment of personal hygiene so that better support the family, the more independent in fulfilling their self-care.Keywords: Elderly, Family Support, Indpendence of the elderly